The effects of high hydrostatic pressure at subzero temperature on the quality of ready-to-eat cured beef carpaccio - Vaudagna, Sergio Ramon (2012)
We compared the application of high hydrostatic pressure (HHP) on unfrozen carpaccio (HHP at 20 °C) and on previously-frozen carpaccio (HHP at −30 °C). HHP at 20 °C changed the color. The pressure increase from 400 to 650 MPa and the time increment from 1 to 5 min at 400 MPa increased L* and b*. a* decreased only with 650 MPa for 5 min at 20 °C. The prior freezing of the carpaccio and the HHP at −30 °C minimized the effect of the HHP on the color and did not change the shear force, but increased expressible moisture as compared to the untreated carpaccio. HHP at 20 °C was more effective in reducing the counts of microorganisms (aerobic total count at 30 °C, Enterobacteriaceae, psychrotrophs viable at 6.5 °C and lactic acid bacteria) than HHP at −30 º C. With HHP at 20 °C, we observed a significant effect of pressure and time on the reduction of the counts.